HUBUNGAN SELF ESTEEM DENGAN RESILIENSI PADA ANAK JALANAN DI KECAMATAN PAYUNG SEKAKI KOTA PEKANBARU - Nofryani, Sizka; Novianti, Ria; Chairilsyah, Daviq (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The aim of this research is to know whether there is a relationship between self esteem and resilience in street children in Payung Sekaki District Pekanbaru City. The population of this research is street children in Payung Sekaki District Pekanbaru City 2-6 years old that consists of 32 children, the samples of this research are 32 street children which taken by using technique of sampling is saturated. Method of this research is Pearson Product Moment relationship to know the relationship between self esteem and resilience in street children in Payung Sekaki District Pekanbaru City. The technique of collecting data used observation sheet in Likert scale form. The technique of analyzing data used scale test and statistic analytical by using SPSS program for Windows ver. 23. Based on hypothesis there is any significant positive relationship between self esteem and resilience in street children in Payung Sekaki District Pekanbaru City. It could be seen from the result of relationship coefficient that rxy = 0,712 and significant level is 0,0000,05. The level of relationship between self esteem and resilience is in the middle category with the rank of determinant coefficient in the amount 50,8%, it means that self esteem affect resilience as much as 50,8%.Key Words: Self Esteem, Resilience